Efektivitas Kinerja: Peran Budaya Organisasi, Komitmen dan Etos Kerja pada kinerja Karyawan di PT Hajma Aruna Java - Eni Rahmawati; Kusuma Chandra Kirana; Selamet Hartanto (Universitas Batanghari Jambi, 2023)
The purpose of this research is to find out how employee performance at PT Hajma Aruna Java is influenced by organizational culture, commitment and work ethic. Questionnaires were a data collection technique in this research with 200 participants as samples. The data analysis method uses multiple linear regression analysis. The results of this research reveal that simultaneously and partially the variables of work culture, commitment and work ethic have a significant effect on the performance of PT employees. Hajima Aruna Java.